Production and emission test of refined coconut oil ethyl ester biodiesel and ethanolysis of crude jatropha oil - Ferrer, Emmanuel Laurea (2009)
This study investigated the production of refined coconut oil ethyl ester biodiesel and well as ethanolysis of crude jatropha oil. It aimed to determine the process conditions for a successful conversion of coconut oil and jatropha oil to ethyl ester biodiesel and to determine whether to product properties conform to Philippine National Standards (PNS) specifications for B100 fatty acid methyl ester biodiesel. This study determined the emission characteristics using a 3.3 kW single-cylinder Sumo diesel engine generator set at varying biodiesel blends and electrical loads with neat automotive diesel oil (ADO) as the base fuel. Preliminary experiments were conducted at different catalyst concentrations and process temperatures. The density, kinematic velocity. Distillation Atmospheric Equivalent Temperature (AET) at 50% and 90% recovery, cetane index, ester content, heating value, acid value, pour point, cloud point, % water content, flash point, total and free glycerine were measured and compared with local standards. Semtech DS emission analyzer was used to study the emission characteristics of the coconut ethyl ester biodiesel at B1, B2 and B5 Blends.
Successful conversion of refined coconut oil to ethyl ester biodiesel via base-catalyzed transesterificaton was carried out at process conditions of 1% (weight to oil) KOH catalyst, 59% excess ethanol, 1.5 hours reaction time and ambient temperature at mixer setting of 4300 to 4500 rpm with an average conversion of 89.5% ester. Several properties of the coconut ethyl ester conformed to the PNS specifications with the exception of acid value and water content. This problem could be eliminated by careful washing and dewatering. Total glycerine was also higher than the local standard but can be resolved by better conversion. The calculated cetane index was 46.327 which is very close to US and Brazil standards for minimum cetane number. Average pour point and cloud point values were below 10 deg.C which is suitable for tropical countries. Both base-catalyzed and two-step esterification of crude jatropha oil via ethanolysis remained unsuccessful due to sensitivity to water but with promisinf result for acid-catalyzed ethanolysis at higher temperature. Emission tests for coconut ethyl ester revealed that the B1 blend had the optimal emission characteristics with most of the parameters while B2 blend had the most significant decrease in CO emission. B1 reduced CO2 emission by 8%, NOx at 7%, THC by 2.5% while excess O2 increased by 3.5% all at 93% (high) electrical load when compared to base petrodiesel. Maximum permissible limits for CO and NOx emissions from a stationary source according to CAA were 437ppmV and 266ppmV, respectively. all blends conformed to CO limit at low and medium load while B1 blend alone conformed to NOx limit at low load. The remaining B2 and B5 blends had an average increase of about 10% and 16% NOx emissions respectively, a typical characteristic for most biodiesels.
Thesis (MS in Environmental Engineering)--University of the Philippines Diliman
Keywords: Coconut oil as fuel; Biodiesel fuels